Dietary generalism accelerates arrival and persistence of coral‐reef fishes in their novel ranges under climate change. (24th July 2020) - Monaco, Cristián J.; Bradshaw, Corey J. A.; Booth, David J.; Gillanders, Bronwyn M.; Schoeman, David S.; Nagelkerken, Ivan
Abstract: Climate change is redistributing marine and terrestrial species globally. Life‐history traits mediate the ability of species to cope with novel environmental conditions, and can be used to gauge the potential redistribution of taxa facing the challenges of a changing climate. However, it is unclear whether the same traits are important across different stages of range shifts (arrival, population increase, persistence). To test which life‐history traits most mediate the process of range extension, we used a 16‐year dataset of 35 range‐extending coral‐reef fish species and quantified the importance of various traits on the arrival time (earliness) and degree of persistence (prevalence and patchiness) at higher latitudes. We show that traits predisposing species to shift their range more rapidly (large body size, broad latitudinal range, long dispersal duration) did not drive the early stages of redistribution. Instead, we found that as diet breadth increased, the initial arrival and establishment (prevalence and patchiness) of climate migrant species in temperate locations occurred earlier. While the initial incursion of range‐shifting species depends on traits associated with dispersal potential, subsequent establishment hinges more on a species' ability to exploit novel food resources locally. These results highlight that generalist species that can best adapt to novel food sources might be most successful in a future ocean. Abstract : Ecologists use life‐history traits to predict which species have the highest probability of redistributing due to climate change. Studies have mostly ignored that range shifts occur in sequential stages (arrival, increase, and persistence), and that different traits are likely important in each stage. Analysing surveys of tropical fishes at the poleward edge of their distribution in Australia, we found that traits predisposing species to shift their range (large size, broad latitudinal range, long dispersal duration) did not drive the early stages of redistribution (arrival time and persistence). Instead, diet breadth was the main contributor to the early stages.